REDESAIN TERMINAL TIRTONADI DENGAN PENDEKATAN GREEN TERMINAL DI SURAKARTA - Nur Aini Prisamsiwi; B. Heru Santosa; Leny Pramesti (Universitas Sebelas Maret Surakarta, 2015)
Transportation is activity of people and goods in moving from one place to another place. Good transportation must be supported by good infrastructures. Transportation infrastructures consist of road, bus stop, bus terminal, rail road, train station, and airport. Bus terminal is one infrastructure which had by every city in Indonesia. Redesigning Tirtonadi Bus Terminal Surakarta is built upon the existing condition of Tirtonadi Bus Terminal in 2013 and the final result of Tirtonadi Bus Terminal development that is not appropriate with Green Terminal concept chosen by the management and the Local Government of Surakarta. This redesign is aimed to obtain appropriate Green Terminal design to change the dirty and polluting image of the bus terminal. The main problem of this design is how to redesign Tirtonadi Bus Station Surakarta by applying Green Terminal Principles. The approach used in this deisgn is Green Terminal principles, they are: ecofriendly builing, eficiency of energy, air quality, water conservation, security, and renewable natural recources management. The result of redesign is Tirtonadi Bus Terminal Surakarta with appropriate Green Terminal concept that the station can be more safe and convenient for the visitors and the building can maintain harmony between architecture and surrounding environment. Keywords: Architecture, Transportation, Redesigning, Bus Terminal, Green Terminal